No effect of artificial gravity on lung function with exercise training during head-down bed rest. Issue 2 (11th August 2015) - Su, Longxiang; Guo, Yinghua; Wang, Yajuan; Wang, Delong; Liu, Changting
Abstract: The aim of this study is to explore the effectiveness of microgravity simulated by head-down bed rest (HDBR) and artificial gravity (AG) with exercise on lung function. Twenty-four volunteers were randomly divided into control and exercise countermeasure (CM) groups for 96 h of 6° HDBR. Comparisons of pulse rate, pulse oxygen saturation (SpO2 ) and lung function were made between these two groups at 0, 24, 48, 72, 96 h. Compared with the sitting position, inspiratory capacity and respiratory reserve volume were significantly higher than before HDBR (0° position) ( P < 0.05). Vital capacity, expiratory reserve volume, forced vital capacity, forced expiratory volume in 1 s, forced inspiratory vital capacity, forced inspiratory volume in 1 s, forced expiratory flow at 25, 50, and 75%, maximal mid-expiratory flow and peak expiratory flow were all significantly lower than those before HDBR ( P < 0.05). Neither control nor CM groups showed significant differences in pulse rate, SpO2, pulmonary volume and pulmonary ventilation function over the HDBR observation time. Postural changes can lead to variation in lung volume and ventilation function, but a HDBR model induced no changes in pulmonary function and therefore should not be used to study AG countermeasures.